Diversity judgments : democratizing judicial legitimacy - Brooks, Roy L. (Roy Lavon), 1950- (Cambridge : Cambridge University Press, 2022)
The US Supreme Court's legitimacy-its diminishing integrity and contribution to the good of society-is being questioned today like no other time in recent memory. Criticisms reflect the perspectives of both 'insiders' (straight white males) and 'outsiders' (mainly people of color, women, and the LGBTQ community). Neither perspective digs deep enough to get at the root of the Court's legitimacy problem, which is one of process. The Court's process of decision-making is antiquated and out of sync with a society that looks and thinks nothing like the America of the eighteenth century, when the process was first implemented. The current process marginalizes many Americans who have a right to feel disenfranchised. Leading scholar of jurisprudence Roy L. Brooks demonstrates how the Court can modernize and democratize its deliberative process, to be more inclusive of the values and life experiences of Americans who are not straight white males.
Introduction : the framework -- Matal v. Tam (trademarking racial slurs) -- Lau v. Nichols (bilingual education) -- Brown v. Board of Education (single race schools) -- Griggs v. Duke Power (employment discrimination) -- District of Columbia v. Heller (The Right to Keep and Bear Arms) -- Roe v. Wade (Reproductive Rights) -- United States v. Virginia (single sex colleges) -- United States v. Morrison (violence against women) -- Kulko v. Superior Court (child custody or support) -- Hernandez v. Texas (equal protection) -- San Antonio Indep. Sch. Dist. v. Rodriguez (school financing) -- Plyler v. Doe (educating undocumented minors) -- Adoptive Couple v. Baby Girl (Indian adoption) -- Obergefell v. Hodges (single-sex marriages) -- Bostock v. Clayton County (employment discrimination) -- EEOC v. Catastrophe Mgt. Solutions Co. (dreadlocks) -- Kelo v. City of New London (eminent domain) -- SFFA v. Harvard (affirmative action) -- McDonald v. Santa Fe Trail Trans. Co. (employment discrimination) -- City of Atlanta v. Rolfe (law enforcement) -- Gideon v. Wainwright (right to counsel) -- Martin v. City of Boise (The Homeless) -- Citizens United v. FEC (campaign financing) -- Trump v. Hawaii (Middle East migrants).
Title from publisher's bibliographic system (viewed on 11 Mar 2022).
Keywords: Discrimination -- Law and legislation -- United States -- Cases; Social justice -- United States -- Cases; Minorities -- Legal status, laws, etc. -- United States -- Cases